1997
DOI: 10.1016/s0014-5793(97)01387-2
|View full text |Cite
|
Sign up to set email alerts
|

c‐Rel and p65 subunits bind to an upstream NF‐κB site in human granulocyte macrophage‐colony stimulating factor promoter involved in phorbol ester response in 5637 cells

Abstract: To further clarify the complex transcriptional regulation of the human GM-CSF gene, which was extensively investigated in activated T cells, we have studied the role of an upstream NF-KB like site in the 5637 non-lymphoid cell line, which derives from a bladder carcinoma and constitutively produces GM-CSF. This sequence, named the A element, has an active role on GM-CSF transcription and is responsive to the tumor promoter PMA in transient transfection experiments. We describe here a heterodimeric binding comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Transfections with intermediate constructs indicated a decrease of activity between pPF2000 (−2010/+26) and pPF20/pPF22 (−1742/+26; −1377/+26) and a significant increase of activity with pPF10 (−1298/+26). This confirmed that the previously described positive element between −2002 and −1984 [5, 6]was effective also in this cell type and suggested the presence of negative regulatory elements.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Transfections with intermediate constructs indicated a decrease of activity between pPF2000 (−2010/+26) and pPF20/pPF22 (−1742/+26; −1377/+26) and a significant increase of activity with pPF10 (−1298/+26). This confirmed that the previously described positive element between −2002 and −1984 [5, 6]was effective also in this cell type and suggested the presence of negative regulatory elements.…”
Section: Resultssupporting
confidence: 90%
“…We previously identified a NF‐κB‐like binding site, located between −2002 and −1984, acting as a positive transcriptional element in the Mo lymphoblastoid cell line [4]. This same NF‐κB‐like binding site participates in response to phorbol ester in 5637 cells derived from bladder carcinoma [5]. These observations suggested that important regulatory elements in distal regions of the GM‐CSF promoter may significantly contribute to the transcriptional regulation of the gene, in physiological and/or pathological conditions, as well as in a tissue‐specific way.…”
Section: Introductionmentioning
confidence: 99%
“…NF-ÎB activation occurs in response to various nonimmune and immune stimuli, and is rapid and highly flexible. This activation has a dual function in the regulation of various immune and inflammatory processes: not only does it lead to coordinated expression of genes whose products promote inflammatory responses [4][5][6], but it also induces apoptosis of activated immune cells [3,7,8], thereby limiting the extent and duration of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors that bind to the CLE0 element include NF-AT, activator protein (AP)-1, surfactant protein (SP)-1, and YY-1 (5,6). A second NF-B binding site ( Ϫ 2,002 to Ϫ 1,984) is also implicated in PMA induction of the GM-CSF promoter and has been shown to bind c-Rel and p65 (7). Further, in response to T-cell receptor activation, an enhancer region, which contains functional NF-AT/AP-1 binding sites and is located 3.3 kb upstream, seems to act in conjunction with the proximal promoter (8,9).…”
mentioning
confidence: 99%